JAMINAN HUKUM BAGI KONSUMEN DALAM MELAKUKAN PEMBELIAN PADA E-COMMERCE DI INDONESIA - Husnulwati, Sri; Hijawati, Hijawati; Yanuarsi, Susi (Solusi, 2024)
The implementation of trade in the world has achieved rapid development. Through this development, an online transaction system was created which can be called E-commerce. This transaction system allows someone to carry out buying and selling activities without meeting face to face. This trend has also spread to Indonesia because it is considered to have many positive impacts. In its implementation, regulations and a clear legal basis are needed to facilitate trade transaction activities, especially in protecting consumer rights. The juridical legal basis has been regulated in UUPK, UU ITE, PP PSTE and UU Criminal Code.